Effects of Blood Flow Restriction on Leukocyte Profile and Muscle Damage - dos Santos, Leandro; Andreatta, Michely V.; Curty, Victor M.; Marcarini, Wena Dantas; Ferreira, Lucas G.; Barauna, Valerio G. (Frontiers in Physiology, 2020)
Purpose: To evaluate muscle damage and the leukocyte profile in response to resistance exercise (RE) with blood flow restriction (BFR) and to compare with high intensity RE. Methods: Twenty volunteers performed the RE in the leg press apparatus in the following groups: RE80, 80% of 1RM (3 x until concentric muscle failure); RE40+BFR, 40% of 1RM with BFR (same total work of RE80 group). The BFR applied was 80% of the total occlusion pressure. Results: There were no differences in the blood leukocyte profile among groups despite the lower exercise-induced muscle damage (EIMD) in the RE40+BFR group. Both groups showed leucocytosis and lymphocytosis immediately after exercise. Leucocytosis and lymphocytosis was greater in the RE40+BFR group. Conclusion: RE associated with BFR was accompanied by a greater leucocytosis and lymphocytosis immediately after exercise, with no difference in neutrophils. This leukocyte blood profile may be related to less muscle damage, as well as faster muscle recovery after 24 and 48h post-exercise.